Meta Analisis Strategi Pembelajaran Agama Islam di Era Digital - Yuni Setia Ningsih (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Learning is dynamic process following development of society over time. Learning any material, including Islamic religious learning, is required to meet the demands of society. So that Islamic religious learning continues to run well in this digital era, a good strategy is needed. This article is the result of meta-analysis research which analyzed several articles in the last five years. This research maps Islamic learning strategies in the digital era. Apart from that, this research also maps the reasons why this strategy has become a mainstay strategy according to the authors of the articles analyzed. Based on the research results, it can be mapped that the strategies presented in these articles are blended learning, participatory and social media-based learning strategies. Furthermore, it was also found that to support strategies that are directly related to learning, there needs to be supporting strategies that must be implemented. These supporting strategies are increasing human resources, developing an integrated curriculum, optimizing digital libraries, improving the quality of education, and digital media literacy. In general, the reason of the article authors presents this strategy is to make learning about Islam more interesting and attractive to the generation in this digital era.